Pendampingan Penyusunan Perangkat Pembelajaran Kurikulum 2013 bagi Guru Madrasah Aliyah - Khalimatus Sadiyah; Mahalli Mahalli; Fathur Rohman; Azzah Nor Laila (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2020)
ABSTRACTThe 2013 curriculum was established by the Ministry of Education and Culture in the middle of the 2013/2014 school year. But until now most of schools have not been implementing it yet. Many new aspects must be adapted by the school, such as administration, learning models, and evaluation systems. So there are still many schools were not totality to implement the 2013 curriculum. One of school that is considered still not total in implementing the 2013 curriculum is Madrasah Aliyah Walisongo Pecangaan Jepara. The contributing factors included the lack of knowledge of MA Walisongo educators in implementing the 2013 curriculum. Looking at the situation, the team of PAI Study Program of the Education Faculty and Teaching Sciences of Unisnu Jepara took the initiative to provide solutions in the form of training and mentoring in the creation of the 2013 curriculum for educators in the madrasah. The target of this training and mentoring is to increase the ability of MA Walisongo educators in preparing learning tools, including learning plans, learning designs, and learning evaluations. The method of implementing this service uses three stages. First, the training was held in two meetings to discuss the theme of the 2013 curriculum concept, syllabus & KI-KD mapping, preparation of the RPP, and practice. Second, mentoring is carried out for four weeks after training. Third, program evaluation with Focus Group Discussion activities with MA Walisongo Pecangaan educators. The results of this service community are the 2013 curriculum learning tools including RPP and 2013 Curriculum Assessment instruments.Â ABSTRAKKurikulum 2013 ditetapkan oleh kemendikbud pada pertengahan tahun ajaran 2013/2014, akan tetapi hingga saat ini masih banyak sekolah yang belum mengimplementasikannya. Banyak aspek baru yang harus diadaptasi oleh sekolah baik dari aspek administrasi, model pembelajaran, maupun sistem evaluasi.Â  Sehingga masih banyak sekolah atau madrasah yang menerapkan kurikulum 2013 setengah-setangah. Salah satu sekolah yang dipandang masih belum total dalam menerapkan kurikulum 2013 adalah Madrasah Aliyah Walisongo Pecangaan Jepara. Faktor penyebabnya antara lain minimnya pengetahuan pendidik MA Walisongo dalam mengimplementasikan kurikulum 2013. Melihat situasi tersebut, maka tim pengabdian Program Studi PAI Fakultas Tarbiyah dan Ilmu Keguruan Unisnu Jepara, berinisiatif memberikan solusi berupa pelatihan dan pendampingan pembuatan perangkat kurikulum 2013 untuk pendidik di madrasah tersebut. Target dari pelatihan dan pendampingan ini adalah peningkatan kemampuan pendidik MA Walisongo dalam menyusun perangkat pembelajaran, meliputi rencana pembelajaran, rancangan pembelajaran, dan evaluasi pembelajaran. Metode pelaksanaan pengabdian ini menggunakan tiga tahapan. Pertama, pelatihan dilaksanakan dalam dua kali pertemuan membahas tema konsep kurikulum 2013, Silabus dan pemetaan KI-KD, penyusunan RPP, dan praktik. Kedua, pendampingan dilakukan selama empat minggu setelah pelatihan. Ketiga, evaluasi program dengan kegiatan Focus Group Discussion bersama para pendidik MA Walisongo Pecangaan. Hasil kegiatan pengabdian ini adalah perangkat pembelajaran kurikulum 2013 meliputi RPP dan Instrumen penilaian Kurikulum 2013.